Adsorption of ruthenium ions on activated charcoal: influence of temperature on the kinetics of the adsorption process - Qadeer, Riaz (Zhejiang University Press, 2005)
Influence of temperature on ruthenium adsorption on activated charcoal from 3 mol/L HNO(3) solutions was investigated in the temperature range of 288 K to 308 K. It was observed that the rise in temperature increases the adsorption of ruthenium ions on activated charcoal and follows the kinetics of first order rate law with rate constant values 0.0564–0.0640 min(−1) in the temperature range of 288 K to 308 K respectively. The activation energy for the adsorption process was found to be 1.3806 kJ/mol. Various thermodynamics quantities namely ΔH, ΔS and ΔG were computed from the equilibrium constant K (C) values. The results indicated a positive heat of adsorption, a positive ΔS and a negative ΔG.